The Efficacy of V. odorata Extract in the Treatment of Insomnia: A Systematic Review and Meta-Analysis - Huang, Shuangfeng; Huang, Qianqian; Zhou, Zhongbao; Zhang, Junliang; Zhan, Yan; Liang, Zhigang (Frontiers in Neurology, 2022)
Aim This systematic review and meta-analysis was performed to assess the effect of Viola odorata (V. odorata) extract in the treatment of insomnia. Methods PubMed, EMBASE, and Cochrane Library databases, as well as references of related articles, were searched. Finally, four articles with five clinical trials including 224 patients were included in the analysis. Results The obtained results indicated a greater improvement in total PSQI scores (MD,−4.67; P = 0.0002), subjective sleep quality score (MD,−0.91; P = 0.003), sleep duration score (MD,−0.77; P < 0.00001), and ISI score (MD,−6.30; P = 0.009) in the Viola extract group compared with the placebo group. However, the Viola extract group did not significantly differ in sleep latency (MD,−0.85; P = 0.08), habitual sleep efficiency (MD,−0.61; P = 0.21), sleep disturbances (MD,−0.36; P = 0.11), and daytime dysfunction (MD,−0.94; P = 0.12) from the placebo group. Conclusions Viola extract supplement led to a greater improvement in total PSQI scores, subjective sleep quality score, sleep duration score, and ISI score compared with the placebo group of patients with chronic insomnia.